PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, LEVERAGE, PERGANTIAN AUDITOR, DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2010-2013) - Nelly Yulinda; Azwir Nasir; Rahmiati Idrus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of independent commissioners, audit committ, leverage, auditor switching and auditor industry specialization on the integrity of the financial report. Independent variables used in this study are independent commissioners, audit commite, leverage, auditor switching and auditor industry specialization, while the dependent variable in this study is the integrity of the financial report are measured using conservatism index (C-Score). Populations used in this study is manufacture companies listed on IDX 2010-2013, where the total population is used by 14 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 56 (14x4). Data analysis conducted with multiple regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables independent commissioners, audit committ, leverage, auditor switching which has a significant influence on integrity of the financial report, while the auditor industry specialization variables did not significantly affect the integrity of the financial report.Keywords : Independent Commissioners, Audit Commite, Leverage, Auditor Switching, and Auditor Industry Specialization